2021
DOI: 10.1159/000509493
|View full text |Cite
|
Sign up to set email alerts
|

3D Technique-Based Nonsurgical Correction of Deformational Congenital Auricular Deformities

Abstract: <b><i>Introduction:</i></b> Congenital auricular deformity (CAD) is a common postpartum deformity, and nonsurgical correction of CAD has been recognized as a safe and effective approach. Three-dimensional (3D) technique has been used in surgical reconstruction of unilateral microtia; however, 3D technique used in nonsurgical correction for deformational CAD has not been reported. <b><i>Methods:</i></b> In this study, 12 CAD patients aged from 0.6 to 7 months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The use of adequate auricular moulding devices in babies presenting with relevant auricular malformations has led to good to very good results in the partial repair of auricular deformities without surgery in recent years [7] . Otoplasty is mostly performed for cosmetic reasons, and it has been observed that people who have undergone the procedure may experience a minor reduction in their hearing compared to those who have not.…”
Section: Introductionmentioning
confidence: 99%
“…The use of adequate auricular moulding devices in babies presenting with relevant auricular malformations has led to good to very good results in the partial repair of auricular deformities without surgery in recent years [7] . Otoplasty is mostly performed for cosmetic reasons, and it has been observed that people who have undergone the procedure may experience a minor reduction in their hearing compared to those who have not.…”
Section: Introductionmentioning
confidence: 99%
“…Multimedia health education presents the links between knowledge in an organized, hierarchical, and radial manner, including the use of illustrations, cartoon pictures, and words [ 9 ]. The complex and disordered thought process is presented with simple and clear pictures to visualize the complex implicit knowledge to some extent [ 10 ]. Patients can reintegrate information through multiple perceptions, such as visual-auditory, to strengthen the imaginative connection between the word picture and the brain, thus improving the healthy development of the mind and body [ 11 ].…”
Section: Introductionmentioning
confidence: 99%